PENGGUNAAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN MATERI HUKUM ISLAM DI SMK NEGERI 1 GUNUNG MERIAH - Lisnawati Butarbutar; Indani (Lembaga Sepercenter, 2025)
This study aims to determine the effectiveness of using educational videos to improve students' understanding of Islamic law at SMK Negeri 1 Gunung Meriah. The research method used was Classroom Action Research (CAR), which was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 30 students in the 11th grade of a specific expertise programme. The research instruments were observation sheets, comprehension tests, and student response questionnaires. The results showed a significant increase in students' understanding of Islamic law material after the implementation of educational videos. In cycle I, student learning completeness reached 70%, and increased in cycle II to 90%. In addition, student responses to the use of educational videos were very positive because they were considered more interesting, easy to understand, and relevant to everyday life. Thus, the use of educational videos can be used as an alternative strategy for Islamic Education teachers in improving the quality of learning in vocational schools.